2022
DOI: 10.1007/s00170-022-08870-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of material removal morphology and prediction of surface roughness based on WEDM successive discharges

Abstract: In this paper, a successive discharges material removal model is proposed to predict the surface roughness of the EN-GJL-250 (Grey Cast Iron) under different discharge parameters of Wire-cut electrical discharge machining (WEDM). Firstly, the finite element method (FEM) was used to analogue simulation the distribution of material surface temperature and flow field in the WEDM single pulse discharge machining process. According to the principle of energy conservation, the surface morphology and characteristic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Enhancement in current further improved the discharge energy. It is further converted into thermal energy which enhances the sparking frequency during NDWEDM [ 81 ]. The formation of recurring spark leads to the melting and vaporization of work material thereby, erosion rate during machining [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enhancement in current further improved the discharge energy. It is further converted into thermal energy which enhances the sparking frequency during NDWEDM [ 81 ]. The formation of recurring spark leads to the melting and vaporization of work material thereby, erosion rate during machining [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…It also shows the temperature distributions across the entire top surface (indicated by a white dashed line) and the interface between the melting material and the substrate (also marked by a white dashed line) [52]. Li et al [56] developed a thermal-fluid coupling model for the single pulse discharge process, utilizing Gaussian heat sources. Their findings indicated that the continuous discharge EDM material removal model exhibited a SR prediction error of 8.26%.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Figure 11(b) shows the development of numerical models based on the literature data reviewed. Most modern works are taking into account the wear of the workpiece within the framework of the technological process [10,41,54,58,62,76,79,83,84,86,91,110,115,135,187,188,191,197,[201][202][203][204][205]. The main technology used in modeling surface changes is the "killing" of elements when a certain material melt temperature is reached with the formation of a new surface type [54,133,135,191,201].…”
Section: Numerical Simulation Of the Edm Processmentioning
confidence: 99%
“…It can be noted that a fairly large number of studies consider the formation of a single crater from a single discharge [41,62,76,79,82,133,135,184,185,197,202,[210][211][212]. Construction of more complex models of shaping is impossible without understanding mathematical description and modeling of the process of crater formation as a whole [202]. There are digital solutions associated with the modeling of multi-pulse processing [62,203,213].…”
Section: Numerical Simulation Of the Edm Processmentioning
confidence: 99%